1997
DOI: 10.1046/j.1365-2958.1997.5501910.x
|View full text |Cite
|
Sign up to set email alerts
|

Phage display selection of peptides against enzyme I of the phosphoenolpyruvate–sugar phosphotransferase system (PTS)

Abstract: SummaryThe bacterial phosphoenolpyruvate-sugar phosphotransferase system (PTS) mediates the uptake and phosphor ylation of carbohydrates and is involved in signal transduction. In response to the availability of carbohydrates it modulates catabolite repression, intermediate metabolism, gene expression and chemotaxis. It is ubiquitous in bacteria but does not occur in animals and plants. Uniqueness and pleiotropic function make the PTS a target for new antibacterial drugs. Enzyme I is the first component of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…The transition state apparently is stabilized by the phosphoryl donor rather than the phosphoryl acceptor protein. This was demonstrated with short basic peptides containing either a histidine or a cysteine that are rapidly phosphorylated by enzyme I but cannot donate the phosphoryl group further to an acceptor protein (37). The inverse mechanism has been observed with CheY, the response regulator of the chemotactic signaling cascade.…”
Section: Discussionmentioning
confidence: 81%
“…The transition state apparently is stabilized by the phosphoryl donor rather than the phosphoryl acceptor protein. This was demonstrated with short basic peptides containing either a histidine or a cysteine that are rapidly phosphorylated by enzyme I but cannot donate the phosphoryl group further to an acceptor protein (37). The inverse mechanism has been observed with CheY, the response regulator of the chemotactic signaling cascade.…”
Section: Discussionmentioning
confidence: 81%
“…In the control experiments, the EI-1 peptide (50 μM) and tetracycline (45 μM) inhibit cell growth drastically. The EI-1 peptide was identified previously as an inhibitor of enzyme I by phage display (Mukhija and Erni 1997). To estimate the IC 50 value of peptide AP1, various concentrations of AP1 (12.5,25,50,100,and 200μM) were grown with the cells.…”
Section: Dna Sequencing Peptide Synthesis and Characterizationmentioning
confidence: 99%
“…Peptides with relatively high-affinity for a variety of interacting molecules can be affinity-isolated from the phage-displayed random peptide libraries (Scott and Smith 1990;Yang et al 2005). Several studies have demonstrated the potential of this technique in discovering new peptides with antimicrobial capability using either whole cells or specific enzymes as the targets (Mukhija and Erni 1997;Paradis-Bleau et al 2008;El Zoeiby et al 2003;BishopHurley et al 2005). In the present studies, the recombinant HPr protein was prepared and used as the target in screening for the peptides that bind tightly with HPr.…”
Section: Introductionmentioning
confidence: 97%
“…In the case of HPr, inactivation is biphasic, initially fast, comparable with what happens with IIA Glc , then slow and linear (not shown). This second phase is probably the result of the continuous regeneration of HPr by slow hydrolysis of its phosphorylated form (56).…”
Section: Pep Analogs Asmentioning
confidence: 99%